The educational system of Andorra - Berengueras Pont, Mercè (Avances en Supervisión Educativa, 2013)
It is interesting to know the educational system of Andorra, by their geographical proximity and sharing in their territory educational performance of its citizens and residents with Spanish and French systems. Also it is interesting is the number of teaching professionals in our country who have worked there and those who currently do their work in this small Pyrenean country.